Plan de negocio para la creación de una empresa dedicada ala producción y comercialización de productos naturales a base de frutas en la ciudad de Cali. - Caicedo Largacha, Hilda Patricia; Cedeño, Diana Marcela (Universidad Antonio Nariño, 2022)
Due to the growth in the market for natural products, a notorious increase in the consumption of fruits is seen, the tendency of the people of Cali to lead a healthy life allows them to contribute to health care through products derived from fruits, therefore, the need to create a company dedicated mainly to contributing positively to the lives of people and families in the capital of Valle del Cauca, offering them 100% natural, nutritional and vitamin products that benefit the human body. Refrescos el paradise SAS has to be constituted as an environmentally friendly business plan, seeking to achieve good economic profitability, maintaining a high rate of satisfaction on the part of the clientele belonging to the capital of Valle del Cauca.